2002
DOI: 10.1007/s00262-002-0325-z
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin-specific antitumor immunity in medullary thyroid carcinoma following dendritic cell vaccination

Abstract: In this study, we investigated the immune response following immunotherapy with calcitonin-pulsed dendritic cells (DC) in 7 patients with metastasized medullary thyroid carcinoma. After immunization with 1-5 x 10(6) autologous DC, significant calcitonin-specific T cell proliferation was detectable in 3 patients. Measurement of cytokine release from T lymphocytes demonstrated high post-treatment interferon-gamma (IFN-gamma) secretion after stimulation with calcitonin in 5 patients, one of whom experienced signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…Toxicity was acceptable, and one partial response was reported. Schott et al reported treatment of seven patients with MTC by immunotherapy with calcitonin-pulsed dendritic cells [47]. One significant response was seen in this preliminary study.…”
Section: Management Of Patients With Persistent or Recurrent Calcitonsupporting
confidence: 49%
“…Toxicity was acceptable, and one partial response was reported. Schott et al reported treatment of seven patients with MTC by immunotherapy with calcitonin-pulsed dendritic cells [47]. One significant response was seen in this preliminary study.…”
Section: Management Of Patients With Persistent or Recurrent Calcitonsupporting
confidence: 49%
“…MTC belongs to the group of neuroendocrine cancers specifically characterized by the expression of calcitonin, 32-aa-long tumor-specific peptide. In the past, we already described that calcitonin may serve as specific tumor Ag useful for vaccination strategies in patients with MTC (21). Following IFN-DC treatment, we now report that two patients do not show any substantial changes in tumor morphology after long-term follow-up.…”
Section: Ifn-dcs As Well As Cd56mentioning
confidence: 57%
“…In addition, three patients developed significant T-cell proliferation of peripheral blood lymphocytes in response to calcitonin and CEA. Peripheral blood lymphocytes drawn after initiation of treatment responded with high-level IFN-g secretion in some patients after stimulation with calcitonin or CEA, whereas the IL-4 production was only slightly increased Endocrine-Related Cancer (2006) 13 779-795 www.endocrinology-journals.org (Schott et al 2002). These data indicate the induction of a Th1-dominated cellular immune response against calcitonin and CEA in the majority of patients.…”
Section: Vaccination Trials In Mtcmentioning
confidence: 87%